Mucoepidermoid carcinoma of the salivary glands. A retrospective study of 51 cases and review of the literatura - Guevara-Canales, Janet O. (2016)
ABSTRACT The aim of this study is to present the casuistic of mucoepidermoid carcinoma of salivary glands in patients diagnosed at “Dr. Eduardo Cáceres Graziani” National Institute for Neoplastic Diseases, Lima, Perú. From January 2002 to December 2012, 51 cases were diagnosed as mucoepidermoid carcinoma. The number of female patients was higher, with 28 cases (54.9%), and regarding age distribution, 33.3% of the patients were under 30 years old. Pain was one of the main symptoms, and 74.5% of the mucoepidermoid carcinomas were located in the parotid gland. It is concluded that epidemiology regarding age and gender of the 51 cases analyzed was in the same range as other studies, and that most cases were located in major salivary glands, in agreement with reports on other populations. Other characte ristics showed a homogeneous distribution.